Cover Image. Issue 1 (January 2017) - Usardi, Alessia; Iyer, Keerthana; Sigoillot, Séverine M.; Dusonchet, Antoine; Selimi, Fekrije
Abstract : Cover: The cover image, by Alessia Usardi et al., is based on the Research Article The immunoglobulin‐like superfamily member IGSF3 is a developmentally regulated protein that controls neuronal morphogenesis, DOI:10.1002/dneu.22412 .